The Impact of Childhood Abuse and Neglect on the Development of Features of Polycystic Ovary Syndrome: A Pilot Study - Akanksha Misra; Olivia Wolfe; Ricardo Azziz (Women's Health Reports)
Objective: To determine associations of childhood emotional and physical abuse and neglect with the incidence of menstrual irregularity, male pattern hair growth, and possible PCOS. Design: Cross-sectional Study at University. Subjects: 410 individuals, 18–45 years old. Intervention: Survey. Main Outcome Measure(s): A questionnaire was administered to students, faculty, and staff at a regional State University of New York (SUNY) campus. Data on sociodemographic factors, menstrual dysfunction (irregularity, male pattern hair growth, and PCOS), and experiences of childhood abuse and neglect were collected. Results: Participants were sub-grouped into those with menstrual irregularity (MI: defined as >35 days between one period’s beginning and the next, or ≤8 cycles/year, or absent periods altogether), or male pattern hair growth (MHG: defined as excess hair on the upper lip, chin, chest, abdomen, buttocks, or back), both (MI+MHG), or those who did have neither (Unaffected). Family income status yielded some association with the presence of MI, MHG, or MI+MHG. There were significant correlations between individuals reporting MI, MHG, and MI+MHG and reported experiences of feeling loved by their caregiver (p value = 0.0029988), experiencing verbal abuse (p value = 0.0000004293), experiencing physical neglect (p value = 0.030228), feeling emotionally disconnected from their caregiver (p value = 0.0006138), and not having a peaceful home (p value = 0.00005760630462), vis-à-vis Unaffected individuals. Almost all respondents with a prior diagnosis of PCOS (97.6%) reported MI and/or MHG. Conclusions: All childhood experiences of abuse and neglect, except the loss of a parent, were significantly associated with features suggestive of PCOS. Larger, unbiased population studies across different demographics, are needed.